Direct Antioxidant Properties of Bilirubin and Biliverdin. Is there a Role for Biliverdin Reductase? - Jansen, Thomas; Daiber, Andreas (Frontiers in Pharmacology, 2012)
Reactive oxygen species (ROS) and signaling events are involved in the pathogenesis of endothelial dysfunction and represent a major contribution to vascular regulation. Molecular signaling is highly dependent on reactive oxygen species. But depending on the amount of ROS production it might have toxic or protective effects. Despite a large number of negative outcomes in large clinical trials (e.g. HOPE, HOPE-TOO), antioxidant molecules and agents are important players to influence the critical balance between production and elimination of RONS. However, chronic systemic antioxidant therapy lacks clinical efficacy, probably by interfering with important physiological redox signaling pathways. Therefore, it may be a much more promising attempt to induce intrinsic antioxidant pathways in order to increase the antioxidants not systemically but at the place of oxidative stress and complications. Among others, heme oxygenase (HO) has been shown to be important for attenuating the overall production of ROS in a broad range of disease states through its ability to degrade heme and to produce carbon monoxide (CO), biliverdin/bilirubin, and the release of free iron with subsequent ferritin induction. With the present review we would like to highlight the important antioxidant role of the heme oxygenase system and especially discuss the contribution of the biliverdin, bilirubin and biliverdin reductase to these beneficial effects. The bilierdin reductase was reported to confer an antioxidant redox amplification cycle by which low, physiological bilirubin concentrations confer potent antioxidant protection via recycling of biliverdin from oxidized bilirubin by the biliverdin reductase, linking this sink for oxidants to the NADPH pool. To date the existence and role of this antioxidant redox cycle is still under debate and we present and discuss the pros and cons as well as our own findings on this topic.